JAK-STAT and the renin-angiotensin system: The role of the JAK-STAT pathway in blood pressure and intrarenal renin-angiotensin system regulation - Satou, Ryousuke (Landes Bioscience, 2012)
The renin-angiotensin system (RAS) plays important roles in blood pressure control and tissue disease. An inappropriate local angiotensin II elevation in the kidneys leads to the development of hypertension, tissue damage and chronic injury. Studies have demonstrated that the JAK-STAT pathway mediates angiotensin II-triggered gene transcription. The JAK-STAT pathway in turn, acting as an amplifying system, contributes to further intrarenal RAS activation. These observations prompt the suggestion that the JAK-STAT pathway may be of importance in elucidating the mechanisms RAS-associated tissue injury. Accordingly, this review provides a brief overview of the interactions between the JAK-STAT pathway and the RAS, specifically the RAS expressed in the kidneys.